2018
DOI: 10.1920/wp.cem.2018.0318
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step non- and semi-parametric predictive regressions for short and long horizon stock return prediction

Abstract: In this paper, we propose three new predictive models: the multi-step nonparametric predictive regression model and the multi-step additive predictive regression model, in which the predictive variables are locally stationary time series; and the multi-step time-varying coefficient predictive regression model, in which the predictive variables are stochastically nonstationary. We also establish the estimation theory and asymptotic properties for these models in the short horizon and long horizon case. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Vogt (2012) states that his convergence result is not valid in a forecasting context. However, Cheng et al (2018) provide predictive models and estimation theory for the local-constant case and locally stationary regressors. They apply their methods to monthly stock market data and find improved predictability of their models compared to traditional linear predictive regression models.…”
Section: The Local-linear Smoothermentioning
confidence: 99%
“…Vogt (2012) states that his convergence result is not valid in a forecasting context. However, Cheng et al (2018) provide predictive models and estimation theory for the local-constant case and locally stationary regressors. They apply their methods to monthly stock market data and find improved predictability of their models compared to traditional linear predictive regression models.…”
Section: The Local-linear Smoothermentioning
confidence: 99%
“…The stock return prediction is one of most popular research topic in financial application [27,31]. This section studies the performance of the hybrid model by MML87 The empirical results show that the hybrid model ARIMA-LSTM can substantially outperform the traditional time series ARIMA model, particularly in the size of forecast window T= 5, 30, 100, 130, 150, and 200.…”
Section: Financial Datamentioning
confidence: 99%
“…This section studies the performance of the hybrid model by MML87 The empirical results show that the hybrid model ARIMA-LSTM can substantially outperform the traditional time series ARIMA model, particularly in the size of forecast window T= 5, 30, 100, 130, 150, and 200. Many studies demonstrated that the stock return depends on various factors such as dividend yield, the book to market ratio, and/or interest rate [27][28][29]. However, traditional linear time series models are difficult to consider the effect of all those factors, it requires a more complex model to capture the information hidden in residual from the ARIMA model.…”
Section: Financial Datamentioning
confidence: 99%
“…There are 10 different 173 parameter sets from p 1 , ..., p 5 and q 1 , ..., q 2 . The values in the table are the average of The stock return prediction is one of most popular research topic in financial 227 application [26,30]. This section studies the performance of the hybrid model by MML87,…”
mentioning
confidence: 99%
“…5, 30, 100, 130, 150, and 200. Many studies demonstrated that the stock 238 return depends on various factors such as dividend yield, the book to market ratio, 239 and/or interest rate[26][27][28]. However, traditional linear time series models are difficult 240 to consider the effect of all those factors, it requires a more complex model to capture Mean, standard deviation, pacf lag 1 to 3 for ten selected stocks…”
mentioning
confidence: 99%